The effect of demonstration methods on the learning of basic makeup (make-up) in children with hearing impairment - Dina Maydinatunnajwa; Reza Febri Abadi; Ratih Listyaningtyas (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2020)
This Research aimed to determine the effect of the Demonstration Method on Basic Learning Makeup in Children with Hearing Impairment Class XII at the Samantha Special School Foundation, Serang City. The method used in this research is Single Subject Research (SSR) with an A-B-A design. The subject is a grade XII child at the Serang City Samantha Special School Foundation who has a hearing impairment. The results showed that the demonstration method had a positive influence on basic learning makeup. This is indicated by the ability of subject W to improve in basic make-up after giving the intervention as evidenced by the percentage score at intervention (B) and baseline 2 (A 2) is higher when compared to the percentage score of baseline 1 (A 1). Achievement of positive results for the subject occurs in the three target behaviours of the subjects in recognizing the basic makeup ingredients, the target behaviour recognising the basic makeup tools, and the target behaviour applying the ingredients and basic face makeup tools. In the target behaviour, 1 subject W in the baseline 1 (A1) phase obtained data with an average of 40%. In the interventions, there have been changes with an average of 80.8%. Whereas in the baseline phase 2 (A2) data were obtained with an average of 66.65%. In the target behaviour of 2 subjects, W in the baseline 1 (A1) phase obtained data with an average of 37.5%. The intervention has experienced a change that is with an average of 79.1375%. Whereas in the baseline 2 (A2) phase, data were obtained with an average of 62.45%. In target behaviour, 3 subjects W in the baseline 1 (A1) phase obtained data with an average of 56.6%. In the interventions, there have been changes with an average of 81.2125%. Whereas in the baseline phase 2 (A2) data were obtained with an average of 66.625%. This Research shows that the demonstration method can influence basic learning makeup in children with hearing impairment in class XII at the Serang City Samantha Special School Foundation.